The network of WHO poliomyelitis regional centres as a strategy against the disease (1954-1963) (Quinto Sol, 2020)
The fear of an influenza pandemic as severe as that of 1918 and the difficulty of obtaining an effective vaccine motivated the WHO to establish a Global Program to fight against this disease in 1947. Its central node was the creation of a World Influenza Centre (London), and around it, a network of regional laboratories dedicated to researching the influenza virus and coordinating the preparation of an effective vaccine. This model was exported to the fight against other pathologies, such as polio. Using unpublished documentation from the historical archive and library of the WHO (Geneva), supplemented by other sources and secondary bibliography, we analyse the process of the creation of the WHO regional polio centre network between 1954 and 1963, when it was reorganised and transformed into centres encompassing all enteroviruses. The development and application of the two different types of vaccine - inactivated (Salk) and attenuated (Sabin) - influenced this initiative, but so too did the international context and the history of the international organization itself. The network contributed to transforming the fight against polio by facilitating the circulation of knowledge, people and scientific-healthcare practices.
Keywords: World Health Organization; prophylaxis; poliomyelitis; regional centres